1995
DOI: 10.1111/j.1745-9125.1995.tb01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Crime Reexamined: The Impact of Religion, Secular Controls, and Social Ecology on Adult Criminality*

Abstract: Since Hirschi and Stark's (1969) surprising failure to find religious (“hellfire”) effects on delinquency, subsequent research has generally revealed an inverse relationship between religiosity and various forms of deviance, delinquency, and crime. The complexity of the relationship and conditions under which it holds, however, continue to be debated. Although a few researchers have found that religion's influence is noncontingent, most have found support—especially among youths—for effects that vary by denomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(178 citation statements)
references
References 47 publications
7
165
3
3
Order By: Relevance
“…Thirdly, while much research has examined the roles of spirituality and religiosity in the juvenile context, this research focused on adults, in whom religiosity and spirituality are not under the direct influence of parents and the consequences of substance abuse are much more severe (Evans et al, 1995;Stack & Kposowa, 2006). The predominance of religiosity studies among juveniles that measured religiosity by frequency of church attendance makes it risky to extrapolate from juvenile to adult behavior because of the issue of forced juvenile church attendance (Cochran, Beeghley & Bock, 1988).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, while much research has examined the roles of spirituality and religiosity in the juvenile context, this research focused on adults, in whom religiosity and spirituality are not under the direct influence of parents and the consequences of substance abuse are much more severe (Evans et al, 1995;Stack & Kposowa, 2006). The predominance of religiosity studies among juveniles that measured religiosity by frequency of church attendance makes it risky to extrapolate from juvenile to adult behavior because of the issue of forced juvenile church attendance (Cochran, Beeghley & Bock, 1988).…”
Section: Significancementioning
confidence: 99%
“…The purpose of this project was to determine if and how religiosity and spirituality affect drug and alcohol abuse. There has been extensive research on religiosity and crime and drug/alcohol abuse; however, the assumption that religiosity and spirituality are protective factors against deviant behavior has been criticized as spurious and requires empirical validation (Cochran, Wood, & Arneklev, 1994;Evans, Cullen, Dunaway, & Burton, 1995).…”
mentioning
confidence: 99%
“…More individualistic-based theories have suggested that religious individuals engage in less delinquent activity (see, for example, Evans et al 1995;Johnson et al 2001;Sloane and Potvin 1986), especially when surrounded by a high proportion of fellow believers (Stark 1996;Stark, Kent, and Doyle 1982). Note that these theories never predict that the number of adherents of different religious traditions will have differing effects on crime rates of communities, nor do they predict that any of these adherents will increase crime rates.…”
Section: Capitalmentioning
confidence: 99%
“…While there are many slight variations using measures from the U.S. Census, we used very frequently used measures that capture classical (Shaw and McKay 1942) Our measure of poverty -calculated based on the proportion of individuals in the block group with income below poverty level -was consistent with the measurement of poverty carried in our prior studies. Our measure of residential instability was calculated as the proportion of renter-occupied housing units, which is consistent with prior research in this area (e.g., Evans et al 1995;Lipton et al 2013;Lockwood 2007;McCord and Ratcliffe 2007;Peterson, Krivo, and Harris 2000;Snowden and Freiburger 10 2015b). Our measure of family disruption was consistent with prior research in this area and was calculated as the proportion of all households in the block group that had a single parent (either female-or male-headed) and with a child under the age of 18.…”
Section: Control Variablesmentioning
confidence: 48%